UTILIZATION OF VERMICOMPOST OF VEGETABLE WASTE FOR PLANTS GROWTH - ANTONY V SAMROT,; VIGNESH V,; VIGNESH MP, (International Journal of Pharma and Bio Sciences, 2015)
Vermicomposting is the process of putrefaction of wastes into organic fertilizer by earthworms. Thus obtained ultimate product is enriched with nutrients like carbon, nitrogen and vital minerals. In this study, earthworm - Eudrilus eugeniae (African night crawlers) were exploited to degrade the pretreated vegetable wastes. Vegetable wastes were found to be degraded in 60-65 days. Thus acquired vermicompost were used as an organic fertilizer against the plants Brassica nigra and Trigonella foenum-graecum, influence of vermicompost on plant growth was observed for 20 days. The vermicompost was found to have positive influence on plant growth.